Metodologia BIM com uso da realidade virtual para o processo de ensino-aprendizagem da disciplina arquitetura e urbanismo do curso de engenharia civil - Aguiar, Cristiane Pereira de (2024)
This dissertation consists of a teaching-learning proposal for the discipline of Architecture and Urbanism involving the development of architectural design integrating Building Information Modeling (BIM) with Virtual Reality (VR). The general objective of this research was to apply a didactic sequence in teaching architectural project development content, contributing to the teaching-learning process of 25 students in the 7th period of the Architecture and Urban Planning discipline of the Civil Engineering undergraduate course at the Institute. Federal Department of Education, Science and Technology of Amazonas – Campus Manaus Centro - IFAM/CMC. It consists of qualitative research, which adopted action research as an investigation strategy to organize methodological procedures through three (03) phases of planning, implementation and monitoring and evaluation, using data collection instruments as: questionnaires, observations, notes in the field diary and evaluation of the architectural projects developed by the participants. The didactic sequence was applied combining face-to-face and flipped classroom study activities. It promoted procedural and attitudinal changes for students, as it encouraged students to apply their knowledge in practical situations, developing their skills and competencies over time and carrying out relevant tasks in their academic lives. The implementation of the planned and detailed didactic sequence occurred in three phases with a workload of 20 hours, including: 12 hours for face-to-face expository and dialogue classes and independent studies, implementation of two workshops held in the computer laboratory, each with lasting 4 hours and in person. Workshop 1 was intended for the student to develop a plan using the Revit/BIM program and workshop 2 lasted 4 hours for viewing the three dimensional project using Virtual Reality glasses. To develop the learning assessment, the students were organized into pairs under the guidance of the researcher participant, they developed 01 residential architectural project from its conception to the visualization of the virtual prototype in 3D. These projects were evaluated using a set of criteria organized into rubrics, thus establishing the level of student performance, difficulties and improvements observed during each phase. The research results demonstrated that the didactic sequence using the integration of BIM with VR offered a meaningful and effective learning experience for Civil Engineering students, improved skills, providing understanding of complex architectural concepts and stimulating creativity in the development of the architectural project. As a result of this research, a Teaching Guide was organized as an educational product under the title 11 “Integration of BIM with virtual reality in teaching architectural projects”, which includes details of the teaching-learning proposal, teaching resources and a set of guidelines that assist teachers and students in the area of Civil Engineering in replicating the aforementioned proposal in their teaching contexts. This study contributes to the existing literature by highlighting the importance of adding the use of Digital Communication and Information Technologies – TDCI as a tool to investigate and improve teaching practices for educators, professionals and researchers interested in promoting the advancement of architecture teaching